Genetic predisposition in pediatric acute myocarditis: a pilot study. (14th October 2021) - Gourzi, P; Pantou, M P; Vagenakis, G; Tsoutsinos, A; Vatsellas, G; Makrythanasis, P; Rammos, S; Degiannis, D
Abstract: Background: Myocarditis is an inflammatory disease of the heart muscle with a wide range of clinical presentations, from asymptomatic to cardiogenic shock and death. Although acute myocarditis is rare in pediatric population, it is caused by common viral infections, like parvovirus B19 or enteroviruses. Limited scientific evidence supports the existence of a genetic background that could underlay the susceptibility to virus-induced myocarditis. Purpose: The aim of the present study was to identify mutations in genes associated with cardiomyopathies, that could possibly underly acute myocarditis in pediatric patients with biopsy-proven parvovirus B19 infection, verified by real time PCR. Methods: Nine pediatric patients presented in our center with acute myocarditis were genotyped with next generation sequencing using Clinical Exome Solution kit (Sophia Genetics) covering 4493 disease-related genes. Variant pathogenicity was accessed according to guidelines by American College of Medical Genetics (2015). Results: Genetic analysis revealed that three of the nine patients were found positive for pathogenic/likely pathogenic mutations in TTR, ABCC6 and SLC22A5 genes. The patient that carried the SLC22A5 variant initially received telbivudine and her ejection fraction was improved from 20% to 45%. Genetic test results suggested that the patient may suffer from mild L-carnitine deficiency. Oral supplementation with high dose of L-carnitine during one month period improved dramatically her EF to normal (65%). The patient that carried the ABCC6 mutation, also carried a variant of unknown significance in MYH7 gene. Four patients carried variants of unknown significance. The variants of unknown significance detected in MYBPC3, SCN5A, and MYH7 genes are of particular interest since they accumulate evidence of pathogenicity. Two patients did not harbor any mutations. Conclusion: A significant proportion of rare variants in genes associated with cardiomyopathies has been identified in a small cohort of pediatric patients with parvovirus-induced acute myocarditis. The findings of our study, although limited, support the existence of a genetic background that could function as a predisposing factor influencing the clinical course of the disease. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Onassis Foundation